Targeting Social Transfers to the Poor in Mexico - Coady, David (IMF Working Papers; Working Paper ;, 2009)
Mexico's main social support program, Oportunidades, combines two methods to target cash to poor households: an initial self-selection by households who acquire knowledge about the program and apply for benefits, followed by an administrative determination of eligibility based on a means test. Self-selection improves targeting by excluding high-income households, while administrative targeting does so mainly by excluding middle-income households. The two methods are complementary: expanding program knowledge across households substantially increases applications from non-poor households, thus reinforcing the importance of administrative targeting. The paper shows that targeting can be further improved through redesigning the means test and differentiating transfers according to demographic characteristics.